Eine theoretische und empirische Analyse der betrieblichen Determinanten von Teilzeitarbeit, Mini- und Midi-Jobs - Christian Pfeifer (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
– The paper examines the company determinants of part-time work and so-called mini-jobs and midi-jobs. The subsample of the IAB establishment panel for Lower Saxony for the period 2000 to 2004 is used for the empirical analysis. From a theoretical viewpoint any of the three employment forms could be used as an instrument of flexible adjustment in the case of demand shocks. The empirical analysis shows, however, that short-term demand shocks have little impact on the probability of a firm using these employment forms and on the intensity to which they are used. One obstacle in the way of reducing working hours are quasi-fixed employment costs. Thus, firms with a larger proportion of skilled employees make less use of part-time work. Overall the results indicate that part-time employment is determined largely by employees' preferences and that marginal part-time work occurs more frequently in establishments without a works council. Moreover, the new regulations concerning part-time employment and mini-jobs, which were introduced in 2001 and 2003 respectively, are likely to encourage the expansion of these two employment forms.
Keywords: 330; Personaleinsatz; Teilzeitarbeit - Determinanten; Mini-Job - Determinanten; IAB-Betriebspanel; institutionelle Faktoren; Arbeitszeitwunsch; Midi-Job; Niedersachsen; Bundesrepublik Deutschland